CD9 promotes TβR2-TβR1 association driving the transition of human dermal fibroblasts to myofibroblast under hypoxia - Wanqi Huang; Ze Zhang; Xin Li; Qingqing Zheng; Chao Wu; Luojia Liu; Ying Chen; Jiaping Zhang; Xupin Jiang (BMC, 2024)
Abstract Background During wound healing, fibroblast to myofibroblast transition is required for wound contraction and remodeling. While hypoxia is an important biophysical factor in wound microenvironment, the exact regulatory mechanism underlying hypoxia and fibroblast-to-myofibroblast transition remains unclear. We previously found that tetraspanin CD9 plays an important role in oxygen sensing and wound healing. Herein, we investigated the effects of physiological hypoxia on fibroblast-to-myofibroblast transition and the biological function and mechanism of CD9 in it. Methods Human skin fibroblasts (HSF) and mouse dermis wounds model were established under physiological hypoxia (2% O2). The cell viability and contractility of HSF under hypoxia were evaluated by CCK8 and collagen gel retraction, respectively. The expression and distribution of fibroblast-to-myofibroblast transition markers and CD9 in HSF were detected by Western blotting and immunofluorescence. CD9 slicing and overexpressing HSFs were constructed to determine the role of CD9 by small interfering RNA and recombinant adenovirus vector. The association of TβR2 and TβR1 was measured by immunoprecipitation to explore the regulatory mechanism. Additionally, further validation was conducted on mouse dermis wounds model through histological analysis. Results Enhanced fibroblast-to-myofibroblast transition and upregulated CD9 expression was observed under hypoxia in vitro and in vivo. Besides, reversal of fibroblast-to-myofibroblast transition under hypoxia was observed when silencing CD9, suggesting that CD9 played a key role in this hypoxia-induced transition. Moreover, hypoxia increased fibroblast-to-myofibroblast transition by activating TGF-β1/Smad2/3 signaling, especially increased interaction of TβR2 and TβR1. Ultimately, CD9 was determined to directly affect TβR1-TβR2 association in hypoxic fibroblast. Conclusion Collectively, these findings suggest that CD9 promotes TβR2-TβR1 association, thus driving the transition of human dermal fibroblasts to myofibroblast under hypoxia.